PEMUDA DAN AJEG BALI DI TENGAH PUSARAN GLOBALISASI - Erviantono, Tedi (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
Youth in Bali do not preceive Ajeg Bali as a stagnant concept but more into a conscious and continued modernization. In their practice, Balinese youth able to defence their identity and culture from new values and culture carried by globalization. Â Key Words: Youth, Ajeg Bali, Globalization.